2024
DOI: 10.1590/1519-6984.253065
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological characteristics of bloodstream infections in a reference hospital in northeastern Brazil

Abstract: Routine blood culture is used for the detection of bloodstream infections by aerobic and anaerobic bacteria and by common pathogenic yeasts. A retrospective study was conducted in a public hospital in Maceió-AL, by collecting data of all medical records with positive blood cultures. Out of the 2,107 blood cultures performed, 17% were positive with Staphylococcus coagulase negative (51.14%), followed by Staphylococcus aureus (11.21%) and Klebsiella pneumoniae (6.32%). Gram-positive bacteria predominated among p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…A maioria dos casos não foi submetido à NPT e HDL, terapias invasivas apontadas na literatura como associadas ao aumento do potencial de risco de IPCSL relacionada à CVC nos pacientes em uso dessas terapêuticas (BRASIL, 2017). Um estudo que avaliou a efetividade e custo do uso de bloqueio antimicrobiano e bloqueio com heparina em pacientes com CVC em uso de NPT, HDL e em pacientes oncológicos, identificou a redução de incidência nos índices acerca da resistência bacteriana não fora investigada nesta pesquisa, contudo a literatura destaca a alta resistência bacteriana sendo um dos agravantes e problemáticas encontradas para o tratamento das infecções (Melo et al, 2023;Lima et al, 2023;Fidelis;Leme, 2022).…”
Section: Resultsunclassified
“…A maioria dos casos não foi submetido à NPT e HDL, terapias invasivas apontadas na literatura como associadas ao aumento do potencial de risco de IPCSL relacionada à CVC nos pacientes em uso dessas terapêuticas (BRASIL, 2017). Um estudo que avaliou a efetividade e custo do uso de bloqueio antimicrobiano e bloqueio com heparina em pacientes com CVC em uso de NPT, HDL e em pacientes oncológicos, identificou a redução de incidência nos índices acerca da resistência bacteriana não fora investigada nesta pesquisa, contudo a literatura destaca a alta resistência bacteriana sendo um dos agravantes e problemáticas encontradas para o tratamento das infecções (Melo et al, 2023;Lima et al, 2023;Fidelis;Leme, 2022).…”
Section: Resultsunclassified
“…Several studies have shown the prevalence of CLABSI caused by Gram-negative organisms, with coagulase-negative Staphylococcus being the main germ ( 19 - 20 ) . These findings corroborate our study, as bacteria from the coagulase-negative Staphylococcus group predominated in the blood cultures (41.4%), and infections may be associated with catheter handling or site colonization during insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos estudios han demostrado la prevalencia de infección de la circulación sanguínea relacionada con catéter venoso central causada por organismos Gram negativos, siendo el Staphylococcus coagulasa negativo el principal germen ( 19 - 20 ) . Estos hallazgos corroboran nuestro estudio, ya que en los hemocultivos predominaron bacterias del grupo de los Staphylococcus coagulasa negativo (41,4%), y las infecciones pueden estar asociadas con la manipulación del catéter o la colonización del sitio durante la inserción.…”
Section: Discussionunclassified
“…The hospital environment has high rates of antimicrobial resistance due to the large handling of hospital antimicrobials in these places, causing a global health problem with estimates of thousands of deaths in the next years (Wu et al, 2021;Melo et al, 2021). In 2017, S. pneumoniae joined the list of 12 priority pathogenic bacteria that was released by the World Health Organization due to of the increase in the rate of infections and resistance to antimicrobials (WHO, 2017).…”
Section: Discussionmentioning
confidence: 99%